2022
DOI: 10.1111/jnu.12793
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and understanding challenges to inform new approaches to improve vaccination rates: A qualitative study in Indonesia

Abstract: Purpose This study aimed to identify and understand challenges to inform new strategies to increase the COVID‐19 vaccination rate according to involved vaccinators' perspectives in Belitung, Indonesia. Design A qualitative descriptive study design was used. Methods Online interviews and chatting were done among 11 vaccinators for data collection between August 2021 and January 2022. Data were analyzed using a content analysis model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Through our study, we found out that vaccine hesitancy, lack of community engagement and over-crowding of vaccine centers are just few of the reasons causing a delay in the vaccination rate. If we dive deep into the issue of 'vaccine hesitancy', "concern about sideeffects is the most common reason for hesitancy" in low to middle income Countries (10). According to our data, many citizens were discouraged when they raised their suspicions about the vaccine.…”
Section: Discussionmentioning
confidence: 77%
“…Through our study, we found out that vaccine hesitancy, lack of community engagement and over-crowding of vaccine centers are just few of the reasons causing a delay in the vaccination rate. If we dive deep into the issue of 'vaccine hesitancy', "concern about sideeffects is the most common reason for hesitancy" in low to middle income Countries (10). According to our data, many citizens were discouraged when they raised their suspicions about the vaccine.…”
Section: Discussionmentioning
confidence: 77%
“…We chose only Muslim students because some previous research showed that there were still some Muslims who believed that they were prohibited from getting vaccinations because the vaccine contained haram materials. 15 , 16 …”
Section: Methodsmentioning
confidence: 99%